The EUROpean and Chinese cardiac and renal Remote Ischemic Preconditioning Study (EURO-CRIPS CardioGroup I): A randomized controlled trial. (15th April 2018) - Moretti, Claudio; Cerrato, Enrico; Cavallero, Erika; Lin, Song; Rossi, Marco Luciano; Picchi, Andrea; Sanguineti, Francesca; Ugo, Fabrizio; Palazzuoli, Alberto; Bertaina, Maurizio; Presbitero, Patrizia; Shao-liang, Chen; et al.
Abstract: Background: The potential protective effects of remote ischemic preconditioning (RIPC) on contrast-induced nephropathy (CIN) after percutaneous coronary intervention (PCI) remain to be defined. Methods and results: A double blind, randomized, placebo controlled multicenter study was performed. Patients younger than 85 years old, with a renal clearance of 30–60 ml/min/1.73 m 2, who were candidates for PCI for all clinical indications except for primary PCI, were allocated 1:1 to RIPC or to standard therapy. The primary endpoint was incidence of CIN. The secondary endpoint was incidence of peri-procedural myocardial infarction (PMI). From February 2013 to April 2014, 3108 patients who were scheduled for coronary angiography were screened for the study. 442 fulfilled the inclusion criteria and 223 received PCI. These patients were randomized to sham RIPC ( n = 107) or treatment group ( n = 116). The only pre-specified subgroup of diabetic patients included 85 (38%) cases. RIPC significantly reduced CIN incidence in the overall population (12.1% vs. 26.1%, p = 0.01, with a NNT = 9) and in non-diabetic patients (9.2% vs. 25.0%, p = 0.02), but showed no benefit in diabetics (16.7% vs. 28.2%, p = 0.21). A trend for lower PMI was seen in the intervention arm (creatine kinase - muscle brain > 5 URL; 8.4% vs. 16.4%, p = 0.07; troponin T > 5 URL; 27% vs. 38%, p = 0.21). Conclusions: Remote ischemic preconditioning significantly reduces the incidence of acute kidney injury in non-diabetic patients undergoing PCI. Larger sample size is presumably needed to assess the effect of RIPC for patients with diabetes mellitus. Clinical Trial number: NCT02195726 https://www.clinicaltrial.gov/ . Highlights: Patients with moderate reduction in glomerular filtration rate were included. Waiting for PCI were randomized to remote ischemic preconditioning (RIPC, n = 116) or sham RIPC (n = 107). RIPC significantly reduced Contrast-Induced nephropathy incidence in the overall population and in non-diabetic patients. Diabetic patients (38% of overall population) showed no benefit in terms of reduced CIN incidence (16.7% vs. 28.2%, p = 0.21).